PENERAPAN MODEL PEMBELAJARAN FIPPED CLASSROM MELALUI METODE KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V111 SMP YP-PGRI MAKASSAR - Thomas Helmon; Andi Taskirah; Muhammad Anas (Jurnal Inovasi Pendidikan dan Sains, 2023)
This research is a classroom action research that aims to improve Biology learning outcomes through the Application of the Makassar Flipped Classroom Learning Model. Data collection was carried out using observation sheets and end-of-cycle tests. The collected data were analyzed using descriptive statistical analysis supplemented with frequency tables. The results showed that there was an increase in student learning outcomes in cycle one, which was in the medium category, namely 13 students or 43.3%, and in cycle two, it was in the high category, namely 17 students or 56.7%. The average increase in student learning outcomes in cycle one was 68.1% and in cycle two it increased to 95% and there was an increase in the completeness of learning outcomes in cycle one, namely 13 students or 43.34% and increased in cycle two, namely 30 students or 84.83 Thus it can be concluded that the application of the Flipped Classroom learning model through Contextual Methods to Improve Student Learning Outcomes in Class V111 SMP YP-PGRI Makassar can be increased.